Aplikasi Belajar Matematika di Sekolah Dasar Negeri 2 Lape Berbasis Android Untuk Meningkatkan Pemahaman Siswa - Hilmy Adrizul Rifqi Hidayat; Shinta Esabella; Jonathan Afriliansyah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to develop an Android-based Mathematics Learning Application as an interactive and engaging learning medium to enhance elementary school students' understanding, particularly at Lape 2 Public Elementary School. The research employs the Waterfall software development model, which consists of five stages: requirements analysis, design, implementation, testing, and maintenance. Data collection was carried out through the distribution of questionnaires as well as the administration of pre-tests and post-tests to fifth-grade students. The application was developed with core features including learning materials, practice questions, automatic scoring, and learning outcome reports. Testing was conducted using the black box testing method to evaluate the application's functionality, and the improvement in students’ understanding was analyzed using the N-Gain method. The results indicate an improvement in students’ understanding, categorized as moderate to high, after using the application. This application is expected to serve as an effective, enjoyable, and relevant alternative learning medium that meets the needs of elementary school students.